Management of Civil Position’s Formation of the Student Youth - Rakhimova, Dinara I.; Kolpakova, Galina V.; Kuznetsova, Tatiana I.; Litvinov, Aleksandr V.; Samokhvalova, Anna G. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the change in relations between the state and civil society in the context of consolidation of many countries’ and communities’ efforts in the fight against terrorism. Modern society demands the training of specialists taking active part in the life activities of civil society. The article aims to find out the specifics of management of civil position’s formation of student youth. The leading approach to the study is a system approach, allowing considering of the management of civil position’s formation as a purposeful process. The article reveals the essence of civil positions; clarifies the managerial features of the civil position’s formation of student youth: the development of knowledge about civil society, rights, freedoms and responsibilities of citizens and the involvement of students on the rights of the entities in legal, moral and political, socio-economic relations for the development of civic actions’ ways, experience’s obtaining to form civil position and emotional-valuable attitude to it. The paper submissions can be useful for managers and teachers of educational institutions; employees of the centers for advanced training and retraining of personnel in the selection and structuring of the content for the training of scientific and pedagogical staff. Keywords: Civil Position, Principle of Purpose, Awareness of the Rights and Duties, Man and Citizen. JEL Classifications: I21, I25, I28